Analisis Pengelolaan Lingkungan Permukiman Di Pinggiran Sungai Kahayan Kelurahan Pahandut Kota Palangka Raya - Milka Milka (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2020)
Management of settlements on the edge of the Kahayan river, pahandut, Palangkaraya city, is part of the way done by the community and assisted by the government to maintain the quality of clean water in the river environment and reduce the disposal of household waste to the river by providing slagging to the community, making MCK / sanitation and communal septic tank. For a literature review on settlement management, the theory used by George R Terry's theory, while the indicators used to determine the process of settlement management that is using the approach of planning, organizing, implementing, and supervising or known as POAC. The research method used is descriptive qualitative. data collection methods using observation, interviews, and documentation. The results of the study revealed that the process of settlement management in the Kahayan river bank, pahandut, palangkaraya city, was running quite well, only that the utilization was not optimal in terms of the settlement management process which consisted of the planning, organizing, implementing, and controlling stages